Impact of prenatal exposure to bisphenol A on pregnant rats: Fetal bone development and immunohistochemistry implications. (February 2019) - Atay, Emre; Ertekin, Tolga; Yılmaz, Halil; Güler, Hatice Susar; Al, Özge; Nisari, Mehtap; Yay, Arzu; Unur, Erdoğan; Özdamar, Saim; Yalçın, Betül
Background: Bisphenol A (BPA) is one of the most commonly produced chemicals in the world. BPA is used in products such as food packaging, personal care products, detergents, and plastic bottles. This study was conducted to determine the effect of BPA on fetal bone development. Material and methods: In this study, 16 pregnant female Sprague-Dawley rats were used. The rats were divided into four groups: the control group and 0.5 mg/kg/day, 5 mg/kg/day, and 50 mg/kg/day dose BPA groups. The skeletal system development of fetuses was examined with double skeletal and immunohistochemistry (IHC) staining (tartrate resistant acid phosphatase (TRAP) and the alkaline phosphatase (AP) expressions) methods. Results: The highest ossification rates in the humerus, radius, and ulna were detected as 41.05%, 39.25%, and 37.26% in the control group, respectively. The highest ossification rates in the femur, tibia, and fibula were detected as 23.04%, 30.73%, and 32.78% in the control group, respectively. Statistically significant differences were found between control and experimental groups in the TRAP and AP expression of the femur by IHC staining ( p < 0.001). Conclusion: Exposure to BPA during pregnancy adversely affected ossification and bone growth. A dose-dependent decrease was observed in the rate of ossification.